PENGARUH SOSIAL EKONOMI DALAM PERLINDUNGAN HAK PEMEGANG INDIKASI GEOGRAFIS (STUDI KASUS KOPI ARABIKA SUMATERA LINTONG DI KABUPATEN HUMBANG HASUNDUTAN PROVINSI SUMATERA UTARA) - HANDIKO PRASETIO SITUMORANG; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Geographical Indications are part of Intellectual Property which is the main drivingfactor for a country's economic development. This Geographical Indication Protection Objectincludes Natural Resources, handicraft products, industrial products owned by an area but notowned by other regions in the Territory of the Unitary State of the Republic of Indonesia. Thistype of protection for Geographical Indications has the peculiarity of other IntellectualProperty Rights Protection, which is characterized by communal ownership and usuallyidentifies the area as its trademark. In writing this thesis, the author tries to examine the Socio-Economic Influence on the Protection of the Rights of Geographical Indications of SumatraLintong Arabica Coffee.The objectives of writing this thesis are: first, to find out the Socio-Economic Effects inProtecting the Rights of Geographical Indications of Sumatra Lintong Arabica Coffee inHumbang Hasundutan Regency. Second, to find out the Efforts That Can Be Taken in Obtainingthe Protection of the Rights of Geographical Indications. The research method in this thesisuses a type of sociological legal research, namely research on the effectiveness of laws that livein society. The nature of this thesis research is research descriptive which describessystematically, the facts and characteristics of the object studied appropriately. The data sourceused is the data source first, seconds and tertiary, the data collection technique in this studywas by interview method, and literature review, then after the data was collected, it was thenanalysed to draw conclusions.Based on the results of the research, the first conclusion can be drawn. The socio-economic impact that occurred on the coffee farmers of the Sumatran Lintong Arabica CoffeeObserver Community (maspekal) as the owner of the right to the geographical indication ofSumatera Lintong arabica coffee is a change in people's lives from previously woodendwellings to semi-permanent and permanent, changes to agricultural management frompreviously only simple tools and using machine tools to help improve farming care and yields,especially coffee. Second, violations committed intentionally and unintentionally must bepursued by legal remedies to prevent further losses to the Sumatra Lintong Arabica CoffeeObserver Community in accordance with Law Number 20 of 2016 concerning Marks andGeographical Indications.Keywords: Geographical Indication-Legal Protection-Legal Remedies.